Diagnóstico y manejo terapéutico de espondilolistesis lumbar degenerativa - Camacho Peralta, Francy Joel (Machala : Universidad Técnica de Machala, 2023)
Degenerative lumbar spondylolisthesis is an uncommon entity that affects between 4 to 6% of the older adult population worldwide, it is more prevalent in male adults, although this disorder has been evidenced in young adults who perform hyperextension sports such as gymnastics. This entity has a multifactorial etiology and is characterized by the translation of a vertebral segment compared to the underlying vertebral segment causing chronic low back pain, neurogenic claudication and radiculopathy. Objective: To describe the diagnostic and therapeutic options available for degenerative lumbar spondylolisthesis by reviewing the scientific evidence. Methodology: A descriptive study of documentary review was carried out in different international databases such as Pubmed, Medscape, Google Academic and Elsevier for the last 5 years. Conclusion: An adequate diagnostic and therapeutic approach to spondylolisthesis in the elderly requires an initial clinical suspicion through a thorough anamnesis and physical evaluation supported by imaging studies. Treatment in the first instance is conservative and the therapeutic alternatives will depend on the severity of the pathology, for symptomatic cases and with increased disability index, surgical treatment is recommended, demonstrating short and long term improvement.
La espondilolistesis lumbar degenerativa es una entidad poco común que afecta entre al 4 al 6% de la población adulta mayor a nivel mundial, se presenta con mayor prevalencia en adultos varones, aunque se ha evidenciado este trastorno en adultos jóvenes que realizan deporte de hiperextensión como la gimnasia. Esta entidad es de etiología multifactorial y se caracteriza por la traslación de un segmento vertebral en comparación al segmento vertebral subyacente ocasionando lumbalgia crónica, claudicación neurogénica y radiculopatía. Objetivo: Describir las opciones diagnósticas y terapéuticas disponibles para la espondilolistesis lumbar degenerativa mediante la revisión de evidencia científica. Metodología: Se realizó un estudio descriptivo de revisión documental en diferentes bases de datos internacionales tales como Pubmed, Medscape, Google Academic y Elsevier de los últimos 5 años. Conclusión: Un abordaje diagnóstico y terapéutico adecuado de la espondilolistesis en el adulto mayor requiere una sospecha clínica inicial realizando una anamnesis y evaluación física minuciosa que se apoya en estudios imagenológicos. El tratamiento en primera instancia es conservador y las alternativas terapéuticas dependerán de la gravedad de la patología, para los casos sintomatológicos y con índice de discapacidad aumentado se recomienda el tratamiento quirúrgico demostrando mejoría a corto y largo plazo.
Keywords: ESPONDILOLISTESIS; CLASIFICACION; DIAGNOSTICO; EJERCICIO FISICO